Presence of risk factors associated with the dissemination of brucellosis to humans in milk processing and slaughtering units of the Manabí province, Ecuador - Zambrano Aguayo, Marina Dalia (2018)
A cross-sectional epidemiological investigation was carried out to determine the risk factors associated with the dissemination of brucellosis to humans in milk processing centres and slaughterhouses in seven cantons of the province of Manabí, Ecuador, between September and November 2015. A census was conducted to quantify farms processing milk, milk processing centres and slaughterhouses. A total of 119 dairy farms, seven slaughterhouses and seven milk processing centres were selected. They were characterized in terms of the types of products produced and on the presence of risk factors as causes of brucellosis in humans. The presence of antibodies against Brucella spp was determined in raw milk by the milk ring test. Results showed that 97.6% of the units make a single product (artisanal cheese). The presence of 85.0% of risk factor was found in milk processing dairies, value higher than that found in the other units (p<0.05). The main risk factors detected related to the facilities were: the presence of other species of animals (100%), no treatment of residuals (85.7%), inadequate workflow (85.7%) and no control of the raw milk (57.1%). The factors related to personnel in the three types of units include the consumption of hazardous foods in all units and the non-periodical serological checks of staff in more than 80% of the units. The use of positive milk to the ring test in the elaboration of milk products was observed, especially in milk processing centres.